Comparative Study on Radio Activity Associated with Common Salt Production Process of Two Salt Works in Kanya Kumari and Tuticorin Districts, Tamil Nadu - Prema Kumari, P.; Mercy Salima, K.; Ethalsha, P. (Asian Journal of Engineering and Applied Technology, 2016)
The manufacture of Common Salt used for the sea brine contain several chemical and radioactive elements. This study estimated the gross alpha and gross beta activites from the sea brine of two salt works at Kovalam in Kanya kumari District and Vepalodai in Tuticorin District, Tamil Nadu. The gross activity was increasing at subsequent stages of production due to the concentration of brine. The sediment and gypsum samples collected at different stages were also subjected for estimation of different types of activity. 40K activity was found to increase, source to bittern from 8.60 ± 0.92 to 221.006± 21.20 Bq l-1at Kovalam salt work and 4.006 ± 0.52 to 162.16 ± 15.94 Bq l-1 at Vepalodai salt work. This study showed that the radio activity is higher in Kovalam salt work than Vepalodai salt work, indicating the influence of naturally high background radiation area.